Platinum-based Treatment for Well- and Poorly Differentiated Pancreatic Neuroendocrine Neoplasms - Pulvirenti, Alessandra (Pancreas, 2021)
OBJECTIVES: Pancreatic neuroendocrine neoplasms include well differentiated tumors (PanNETs) and poorly differentiated carcinomas (PanNECs). Previous reports suggested a role for platinum-based therapy largely in PanNEC. We sought to investigate the role of platinum-based therapy in pancreatic neuroendocrine neoplasms regardless of tumor grade and differentiation. METHODS: Patients with pancreatic neuroendocrine neoplasms treated with platinum-based therapy at Memorial Sloan Kettering (1994–2016) and Verona University Hospital (2008–2016) were retrospectively identified. Response to treatment by RECISTv1.1, overall survival and progression-free survival were defined. Among patients with available tissue, DAXX, ATRX, Rb, and p53 expression was evaluated to support the histologic grade of differentiation. RESULTS: Fifty PanNETs, 29 PanNECs, and 22 high grade tumors with undeterminable differentiation were included. No patients achieved complete response. Overall rate of partial response was 31%, 41% for PanNEC and 20% for PanNETs. Among PanNETs, PR was achieved in 33% of G1 (2/6), 10% of G2 (2/19), and 24% of G3 (6/25) tumors. Median overall survival was 29.3 months for PanNETs and 10.9 months for PanNEC (P <0.001). There was no significant difference in median progression-free survival (P = 0.2). CONCLUSIONS: Platinum-based therapies demonstrated increased activity in PanNEC, however promising efficacy was also observed in PanNETs, irrespective of grade.